Competition‐mediated feedbacks in experimental multispecies epizootics. Issue 3 (March 2016) - Dallas, Tad; Hall, Richard J.; Drake, John M.
Abstract: Competition structures ecological communities and alters host–pathogen interactions. In environmentally transmitted pathogens, an infection‐resistant competitor may influence infection dynamics in a susceptible species through the negative impacts of competition (e.g., by reducing host density or causing nutritional stress that increases susceptibility to infection) and/or the positive impacts of reducing transmission efficiency (e.g., by removing environmental pathogen stages). Thus, a non‐susceptible competitor may enhance, reduce, or have no net effect on susceptible host density and infection prevalence. Here, we couple an epidemiological model with experimental epidemics to test how resource competition with a non‐susceptible competitor ( Daphnia pulicaria ) influences fungal microparasite ( Metschnikowia bicuspidata ) infection dynamics in a susceptible host species ( D. dentifera ). Our model and experiments suggest that competitor density can mediate the direction and magnitude of the effect of competition on infection dynamics, with a peak in infection prevalence occurring at intermediate competitor densities. At low densities, the non‐susceptible competitor D. pulicaria may reduce infection prevalence in the susceptible host by removing fungal spores from the environment through feeding. However, when competitor density is increased and resources become limiting, D. pulicaria negatively impacts the susceptible host by increasing susceptible host feeding rates, and therefore fungal spore intake, and further by reducing susceptible host population size as it is driven toward competitive exclusion. In conclusion, these results show that a tradeoff between the competitor as a consumer of pathogen, which serves to reduce epidemic size, and as a modifier of susceptible host foraging ecology, which influences infection rates, may alternately enhance or dampen the magnitude of local epidemics.